2006
DOI: 10.1080/10428190500301140
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of primary granulocytic sarcoma by non-myeloablative stem cell transplant

Abstract: Pre-leukemic granulocytic sarcoma (GS) may pose an initial diagnostic problem and its therapeutic approach has never been formally established. To our knowledge, non-myeloablative stem cell transplantation has been reported in cases of leukemic GS, but not in primary GS. We report a case of primary GS with extensive and aggressive presenting features and successfully treated with intensive chemotherapy followed by non-myeloablative allogeneic stem cell transplant. This resulted in complete remission with minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…More aggressive modalities such as allogeneic HSCT are alternative strategies for isolated MS. In previous studies, the mean disease-free survival time of 12 patients who received allogeneic or autologous HSCT was reported to be 27.3 months (12–48 mo) [ 27 28 29 ]. Our patient underwent allogeneic HSCT from a human leukocyte antigen (HLA)-matched sibling donor, in addition to surgery and intensive chemotherapy, and remains disease-free after 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…More aggressive modalities such as allogeneic HSCT are alternative strategies for isolated MS. In previous studies, the mean disease-free survival time of 12 patients who received allogeneic or autologous HSCT was reported to be 27.3 months (12–48 mo) [ 27 28 29 ]. Our patient underwent allogeneic HSCT from a human leukocyte antigen (HLA)-matched sibling donor, in addition to surgery and intensive chemotherapy, and remains disease-free after 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…2 Histology of the surgical specimen demonstrated diffuse infiltration of medium to large cells with conspicuous nucleoli. a HE staining, b immunohistochemical staining of CD34, and c myeloperoxidase staining publication [6,[13][14][15][16][17][18][19]. Their mean disease-free survival period was reported to be 27.3 months (12-48 months) after stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no prospective trials evaluating the role of BMT/HSCT in primary GS, some retrospective studies have shown good results with a 5-year survival rate of 48% and even encourage considering allogenic BMT/HSCT after the patients’ first induction of remission. [ 53 55 ]…”
Section: Discussionmentioning
confidence: 99%